2018
DOI: 10.1590/1807-1929/agriambi.v22n11p770-775
|View full text |Cite
|
Sign up to set email alerts
|

Saline stress and potassium/calcium ratio in fertigated eggplant

Abstract: In order to evaluate the effect of irrigation water salinity in interaction with different potassium and calcium ratios applied through fertigation in eggplant, an experiment was carried out at the Department of Environmental and Technological Sciences of the Federal Rural University of the Semi-Arid Region, in Mossoró, RN, Brazil. The experimental design was randomized blocks, in a 5 x 4 factorial scheme, with four replicates. The treatments were obtained by the combination between five ionic ratios of potass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
5
7
0
Order By: Relevance
“…These results show that the use of saline water can cause reduction in fruit size, confirming the information presented by other authors (Santos et al, 2016;El-Mogy et al, 2018), as observed in other solanaceous crops, such as eggplant (Santos et al, 2018) and bell pepper (Oliveira et al, 2018;Dias et al, 2019;Santos et al, 2019;Silva et al, 2020).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These results show that the use of saline water can cause reduction in fruit size, confirming the information presented by other authors (Santos et al, 2016;El-Mogy et al, 2018), as observed in other solanaceous crops, such as eggplant (Santos et al, 2018) and bell pepper (Oliveira et al, 2018;Dias et al, 2019;Santos et al, 2019;Silva et al, 2020).…”
Section: Resultssupporting
confidence: 90%
“…These results demonstrate that the fertigation treatments F1, F4 and F5, which applied higher concentrations of either K (F1) or Ca (F4 and F5), were not efficient to mitigate the effect of salinity on NFR, thus being consistent with the result observed by Tuna et al (2007) and Santos et al (2018), when working with hydroponic tomato and eggplant plants, respectively, subjected to salinity and calcium levels in nutrient solution. These authors also found that the increase in calcium concentration did not reduce the effect of salt stress on the number of fruits.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Salinity is an abiotic stress which limits plant growth and yield worldwide. The excess of salts in many regions of arid and semiarid areas constitutes a serious obstacle for the production system, due to both the changes in soil physical and chemical attributes and the action of specific ions such as Na + and Cl - (Santos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to Medeiros et al (2017), under semiarid conditions, it is possible to produce eggplant using wastewater, minimizing the application of mineral fertilizers. Santos et al (2018), studying salt stress in eggplant, observed that the variables yield, length, fresh mass and number of fruits per plant decreased with the increase in irrigation water salinity.…”
Section: Introductionmentioning
confidence: 99%